Mixed infections of fungal trunk pathogens and induced systemic phenolic compound production in grapevines - Wallis, Christopher M.; Gorman, Zachary; Galarneau, Erin R. -A.; Baumgartner, Kendra (Frontiers in Fungal Biology, 2022)
As grapevines mature in California vineyards they accumulate chronic wood infections by the Ascomycete fungi that cause trunk diseases, including Botryosphaeria dieback (caused by Diplodia seriata and Neofusicoccum parvum) and Esca (caused by Phaeomoniella chlamydospora). It is thought that such mixed infections become localized to separate internal lesions/cankers of the permanent, woody structure of an individual vine, but nonetheless the fungi all colonize the same vascular system. In response to infection by one pathogen, the host may initiate systemic biochemical changes, which in turn may affect the extent of subsequent infections by other pathogens. To test this hypothesis, we measured changes in phenolic compounds in the wood and lesion lengths of the pathogens, during sequential co-inoculations with different or identical pair-wise sequences of infection by D. seriata, N. parvum, or P. chlamydospora. Prior fungal infections only affected the development of subsequent D. seriata infections. Effects of fungal infections on phenolic compounds were variable, yet initial infection by D. seriata was associated with significantly higher concentrations of most phenolic compounds distally, compared to all other initial inoculation treatments. It was hypothesized that pre-existing phenolic levels can slow initial lesion development of fungal trunk pathogens, especially for D. seriata, but over time the pathogens appeared to overcome or neutralize phenolic compounds and grow unimpeded. These results demonstrate that effects of one fungal trunk pathogen infection is generally unable to distally affect another long-term, albeit shifts in host phenolics and other plant defenses do occur.